- #1

- 31

- 0

## Homework Statement

dx/dt + dy/dt = 2x + 2y + 1

dx/dt + 2(dy/dt) = y + 3

## Homework Equations

## The Attempt at a Solution

Dx + Dy = 2x + 2y + 1

Dx + 2Dy = y + 3

--Rearranging----------------------------

Dx - 2x = -Dy + 2y + 1

Dx = -2Dy + y + 3

---Factoring-----------------------------

(D - 2)x = (-D + 2)y + 1

Dx = (-2D + 1)y + 3

--Eliminating x--

(D)(Dx-2x) = ((-D+2)y + 1) (D) <--- multiply by D

-(D-2)(Dx) = ((-2D + 1)y + 3) -(D-2) <---- multiply by -(D-2)

I get to this point and try to cancel out terms but it becomes a mess and attempting to find the solution usually leaves my with polynomials I can't factor, I don't know what to do..